Vesicular lichen nitidus - Lin, Shangqing; Wang, Xiaohui; Lin, Mengjie; Ren, Jun (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
A 33-year-old man was presented with flat-topped lesions distributed over the limbs and trunk accompanied with occasional pruritus for nearly 8 years. No other cutaneous or mucous lesions were detected. He denied any significant medical problems or family history. On examination, there were discrete, grouped, flesh-coloured, flat-topped papules or vesicles measuring 1 to 2 mm in diameter distributed over the limbs and lower abdomen (Figure 1 A). Histopathological examination showed the focal degeneration of the basal layer with obvious separation of epidermis immediately beneath well-circumscribed lymphohistiocytic cells infiltrating like “ball-in-claw” rete ridges (Figure 1 B). To further determine the histologic origin of vesicles, immunohistochemistry of CD31/CD34 (blood vessel marker) and D2-40 (lymphatic vessel marker) was performed. But no positive staining of vesicles was found (Figures 1 C, D). Based on clinical and histopathological findings, we further confirmed the final diagnosis of vesicular lichen nitidus (VLN). However, the lesions were hardly improved after topical corticosteroids.